Assessing environmental sustainability in Colombia: Metrics and policy recommendations - Estefany Garces; Carlos J. Franco; Arkaitz Usubiaga-Liaño; César Augusto Ruiz-Agudelo; Alison Fairbrass (Environmental and Sustainability Indicators)
Colombia faces significant challenges in environmental sustainability, despite its biodiversity-rich status. This study applies the Environmental Sustainability Gap (ESGAP) framework, assessing the nation's environmental sustainability through the Strong Environmental Sustainability Index (SESI) and Progress Index (SESPI). Our findings reveal a critical SESI score of 33 out of 100, indicating a substantial gap between current and sustainability conditions, particularly in areas like CO2 emissions and reforestation. Notable achievements include progress in reducing the consumption of ozone depleting substances and enhancing access to clean cooking technologies. The study underscores the urgency of complementing the insights provided by the Sustainable Development Goals with environmental sustainability indicators as proposed by the ESGAP. This approach reveals blind spots in Colombia's environmental policies and prioritizes areas needing urgent attention.